A Systematic Quantitative Approach to Rational Drug Design and the Discovery of Novel Human Antigen R (HuR) Inhibitors - Dey, Juhi; Kaushiki, Kumari; Mishra, KM Abha; Sudheer, Paga; Sethi, Kalyan Kumar (Anti-Cancer Agents in Medicinal Chemistry, 2025)
Background1,4-Naphthoquinone and its derivatives are recognized for their potent anticancer effects, establishing this pharmacophore as a key focus in cancer research. Their potential to modulate cellular pathways suggests they could be effective in developing new HuR inhibitors, targeting a protein crucial for regulating cancer-related gene expression. Compounds C1-C20 were designed by using Discovery Studio (DS) software.MethodsIn this study, a systematic approach involves scaffold hopping followed by additional research such as molecular docking, ADMET, drug-likeness, toxicity prediction, molecular dynamic (MD) simulation, and binding free energy analysis was used to discover novel Human Antigen R (HuR) inhibitors.ResultsIn molecular docking, 1,4-Naphthoquinone derivatives showed better interactions with the HuR protein compared to that of the conventional HuR inhibitor MS-444. Among twenty 1,4-Naphthoquinone derivatives, most of the compounds showed favorable pharmacokinetic characteristics. In the toxicity prediction model, most of the designed compounds were neither mutagenic nor carcinogenic. According to MD simulation, C5 is more stable than MS-444.ConclusionThe designed 1,4-Naphthoquinone derivatives have been found to be crucial structural motifs for the discovery of novel HuR inhibitors, which was well supported by the in-silico screening and molecular modeling methods.
Keywords: 1; 4-naphthoquinone